Altered sucking dynamics in a breastfed infant with Down syndrome: a case report - Viviane Silva Coentro; Donna T. Geddes; Sharon L. Perrella (BMC, 2020)
Abstract Background The health and developmental advantages of human milk and breastfeeding are particularly important for infants with Down syndrome. However, they typically have shorter breastfeeding duration due to sucking issues that are not well understood. This case report describes serial measures of milk transfer volumes, sucking dynamics and tongue movement in a breastfeeding infant with Down syndrome. Management of maternal milk production enabled feeding of only breast milk until maturation of breastfeeding skills and the achievement of full breastfeeding by 6 months. Case presentation The mother of a term infant with Down syndrome and no associated health complications presented with concerns regarding adequacy of milk removal at the breast and low milk supply. We monitored sucking dynamics during breastfeeding by measuring intraoral vacuum strength, nutritive and non-nutritive suck rates and burst durations, and tongue movement using submental ultrasound. Breastfeeds were monitored at 4, 10, 14, 19 and 24 weeks, and maternal 24 h milk production was measured at 4, 10 and 24 weeks postpartum. We observed a weaker suck strength and shorter nutritive suck duration, and atypical tongue movement up to 19 weeks, with low milk transfer volumes. Regular breast expression was effective in increasing maternal milk production, providing expressed milk for all complementary feeds. Full breastfeeding was achieved by 6 months when reference sucking values were observed. Conclusions This case report illustrates that infants with Down syndrome may have low intraoral vacuum and limited nutritive sucking that persists for several months, likely due to delayed oro-motor development. In the absence of effective sucking human milk feeding can continue when milk production is stimulated with frequent and adequate breast expression. It is possible for infants with Down syndrome and no associated health complications to eventually establish full breastfeeding. Mothers that wish to breastfeed their infant with Down syndrome require anticipatory guidance and continuing lactation and family support.